Antimicrobial Effects of Four Intracanal Medicaments on Enterococcus Faecalis: An in Vitro Study - Mozayeni, Mohammad Ali; Haeri, Ali; Dianat, Omid; Jafari, Ali Reza (Iranian Endodontic Journal, 2014)
Introduction: The aim of this in vitro study was to evaluate the antimicrobial activity of four intracanal medicaments on Enterococcus Faecalis (E. Faecalis). Methods and Materials: Fifty extracted single-rooted human teeth were prepared with standard method. After contaminating the canals with E. Faecalis, the samples were divided into one control and four experimental groups (n=10). The teeth in each group were treated with one of the experimental medicaments, including calcium hydroxide (CH), 2% chlorhexidine (CHX), triple antibiotic paste (TAP) and nanosilver (NS). In control group, canals were filled with neutral gel. Microbial samples were obtained from the roots after 7 days and optical density of the cultures was determined after 24h incubation. Optical density values were analyzed with one-way analysis of variance and Tukey’s post hoc tests. Results: CHX gel and TAP were significantly more effective against E. Faecalis than CH, which was also significantly more efficient than NS and normal saline. In the paper cone samples, CHX gel was more effective than TAP; however, samples obtained with #2 and 4 Gate Glidden drills, indicated that TAP was much more efficient than CHX gel. Normal saline and NS had similar effects on E. Faecalis. Conclusion: Nanosilver gel was not efficient enough against E. Faecalis; however, TAP and CHX gel showed better antibacterial efficacy than CH and can be used as an alternative intracanal medicament in root canal therapies.